2015
DOI: 10.3390/mi6091387
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Self-Assembled Microparticle Chains by Electroosmotic Flow Assisted Electrorotation in an Optoelectronic Device

Abstract: A method incorporating the optically induced electrorotation (OER) and alternating current electroosmotic (ACEO) effects, for the formation and motion control of microparticle chains, is numerically and experimentally demonstrated. In this method, both the rotating electric field and ACEO fluid roll are generated around the border between light and dark area of the fluidic chamber in an optoelectronic tweezers (OET) device. The experimental results show that the particle chains can self-rotate in their pitch a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…For example, many cells exhibit unique self-rotation behaviors in OET systems, which can be used as a label-free biomarker to rapidly identify and characterize cells of different kinds. [180][181][182] Although the mechanism responsible for self-rotation of cells in OET still remains debatable, [181][182][183][184][185][186][187][188] it is demonstrated that the rotation is determined by the electric field (i.e., frequency and field intensity) and polarization properties of cells. Fig.…”
Section: Cell Analysismentioning
confidence: 99%
“…For example, many cells exhibit unique self-rotation behaviors in OET systems, which can be used as a label-free biomarker to rapidly identify and characterize cells of different kinds. [180][181][182] Although the mechanism responsible for self-rotation of cells in OET still remains debatable, [181][182][183][184][185][186][187][188] it is demonstrated that the rotation is determined by the electric field (i.e., frequency and field intensity) and polarization properties of cells. Fig.…”
Section: Cell Analysismentioning
confidence: 99%
“…The detailed information could be found in Ref. [49]. The microparticle chain can be self-assembled under an e-field E, and then, a polarization could be induced in the particle chain.…”
Section: Experiments Setup and Working Principlementioning
confidence: 99%
“…[28][29][30] Additionally, these methods can be combined for enhanced effectiveness. 31 Mischel et al introduced a sinusoidal excitation voltage with a 90°phase difference across four electrodes, which could generate a uniform rotating electric field for electrokinetic rotation. 32 Moreover, Huang et al proposed a novel ROT technique for three-dimensional electrokinetic rotation of particles, achieving 3D rotation with the control of direction and speed.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al combined optical-induced electric rotation (OER) with alternating current electroosmosis (ACEO) to control the rotational motion of particle chains through numerical simulations and experiments. 34 In order to achieve vertical rotation and rolling phenomena of particle chains, Zhao et al introduced a newly developed volumetric polarization and integration (VPI) method to study the movement of pearl chains under DEP in a flow condition. 35 Furthermore, Cheng et al achieved the electric rotation of particle polymers through parallel plate electrodes and inter-particle forces.…”
Section: Introductionmentioning
confidence: 99%